(untitled) (GYMNASIUM, 2017)
In present research we presuppose that the basketball’s free throw is perfectible, and the implementation of some exercises structures for free throws perfection goes to players development, a bigger number of scored points, special tactic for ending periods of games, taking winnings games, at least in those wich the final result depend on a scored free throw. The importance of basketball’s free throw from game statistics shows that at this age and this team from all scored points the free shots represent 24 %. In our first league, SC Municipal Târgoviște, the champions of 2013-2014 National Championship has 71,8 % free throws made per season, with an average of 14,4 free throws made from 20 tryed, from the average of 86,2 points made per game, 16,7 % being free throws made.